Exploring Total Rewards Management and Employee Retention: Evidence from the Non-Profit/NGO Sector - Airrykah Ehi EHEBHAMHEN (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: This study uniquely integrates systematic review and qualitative analysis to contextualise TRM within the NGO environment, to understand how reward systems influence employees’ decisions to remain with their organizations. Methodology: A qualitative approach was adopted, beginning with a systematic review of existing literature to identify reward practices linked to employee retention across sectors. This was followed by a thematic analysis of data drawn from a diverse range of non-profit/NGO organizations to examine prevailing TRM practices and their effects on employee retention. Results and Findings: The findings indicate that TRM practices are both directly and indirectly associated with employee retention. Employees are more likely to remain in organizations that offer well-balanced combinations of monetary and non-monetary rewards. The study also reveals that organizational context, including institutional characteristics, funding arrangements, and workforce composition, significantly moderates the effectiveness of TRM practices. Novelty: By integrating systematic review evidence with qualitative insights, this study introduces a novel approach to examining Talent Relationship Management (TRM) practices within the non-profit/NGO sector. Originality: This research contributes to the limited empirical literature on TRM in the non-profit/NGO sector, emphasizing the importance of context-specific reward strategies in fostering employee retention. Conclusion: The study concludes that strategically aligned and context-sensitive TRM practices are essential for improving employee retention and supporting sustainable talent management in non-profit/NGO organizations. Type of Paper: Research article.